Anisotropic Black Phosphorus Synaptic Device for Neuromorphic Applications. Issue 25 (27th April 2016) - Tian, He; Guo, Qiushi; Xie, Yujun; Zhao, Huan; Li, Cheng; Cha, Judy J.; Xia, Fengnian; Wang, Han
Abstract : The first black‐phosphorus synaptic device is demonstrated, which offers intrinsic anisotropy in its synaptic characteristics directly resulting from its low crystalline symmetry. Key features of biological synapses, such as long‐term plasticity with heterogeneity, including long‐term potentiation/depression and spike‐timing‐dependent plasticity, are mimicked. This demonstration represents an important step toward introducing intrinsic heterogeneity to artificial neuromorphic systems.